Regulating pesticides in food : the Delaney paradox - National Research Council (U.S.). Committee on Scientific and Regulatory Issues Underlying Pesticide Use Patterns and Agricultural Innovation (Washington, D.C. : National Academy Press, 1987)
Concern about health effects from exposure to pesticides in foods is growing as scientists learn more about the toxic properties of pesticides. The Delaney Clause, a provision of the Food, Drug and Cosmetic Act, prohibits tolerances for any pesticide that causes cancer in test animals or in humans if the pesticide concentrates in processed food or feeds. This volume examines the impacts of the Delaney Clause on agricultural innovation and on the public's dietary exposure to potentially carcinogenic pesticide residues. Four regulatory scenarios are described to illustrate the effects of varying approaches to managing oncogenic pesticide residues in food.
Introduction -- The current system : theory and practice -- Estimates of dietary oncogenic risks -- The scenarios and the results -- Comparing the impact of the scenarios -- Pesticide innovation and the economic effects of implementing the Delaney Clause -- Appendixes. A. Legislative history of the Pesticide Residues Amendment of 1954 and the Delaney Clause of the Food Additives Amendment of 1958 / Bruce S. Wilson -- B. Analytical methodology for estimating oncogenic risks of human exposure to agricultural chemicals in food crops / John P. Wargo -- C. Case studies of the EPA's application of the Delaney Clause in the tolerance-setting process / Richard Wiles -- D. Pesticide innovation. Trends in innovation / Earl R. Swanson ; Weed control / Fred H. Tschirley ; Insect control / T. Roy Fukuto -- E. Survey of pesticide R & D directors : how do current laws affect agricultural pesticide research productivity?
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Pesticide residues in food -- Law and legislation -- United States; Food additives -- Law and legislation -- United States; Pesticide residues in food -- United States; Food additives -- United States; Pesticides -- Environmental aspects; Pesticides -- Toxicology; Food Additives -- legislation & jurisprudence; Pesticide Residues; United States; Pesticides -- Politique gouvernementale -- ¡tats-Unis; Pesticides -- Toxicologie; Pesticides -- Řsidus dans les aliments; Pesticides -- Résidus dans les aliments -- États-Unis.; Aliments -- Additifs -- États-Unis.; Pesticides -- Résidus.; POLITICAL SCIENCE -- Government -- Judicial Branch; LAW -- Legal Services; LAW -- Civil Procedure; LAW -- Administrative Law & Regulatory Practice; Législation alimentaire; Résidus de pesticides; Etats-Unis d'Amérique.; Pesticides -- Toxicology; Pesticides -- Environmental aspects; Food additives; Food additives -- Law and legislation; Pesticide residues in food; Pesticide residues in food -- Law and legislation; United States